Reaksi Pasar Modal terhadap Pengumuman Pemberlakuan Undang-Undang Nomor 7 Tahun 2021 tentang Harmonisasi Peraturan Perpajakan - Hari Putri, Ni Made Dini; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 34 No 1 (2024)DO - 10.24843/EJA.2024.v34.i01.p06, 2024)
The announcement of the implementation of government policies, especially reform of tax regulations, indicates a change in tax management and the amount of tax obligations that must be borne. The aim of this research is to obtain empirical evidence that the capital market reacted to the announcement of the implementation of Law Number 7 of 2021 concerning Harmonization of Tax Regulations. This research is an event study with a window period of 7 trading days. The location of this research is the Indonesian Stock Exchange with a population of 728 companies. Samples were taken using a proportioned stratified random sampling technique of 258 companies. The analysis technique used is the one sample t-test on cumulative abnormal return (CAR). The test results show that there is no market reaction as seen from the absence of significant abnormal returns around the event date. Keywords: Event Study; Abnormal Return; Harmonization of Tax Regulation; Stock Market Reaction